2006
DOI: 10.1177/0042085905282249
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Cultural Identity and Culture-Based Educational Programs for Urban American Indian Students

Abstract: Extant survey data collected from 240 urban American Indian students were used to examine the impact of culture-based and universally accepted effective practices in education on American Indian educational outcomes. The results found that culture-based programs had a largely indirect effect, affecting students'educational outcomes via universal constructs, such as a safe and positive school climate, parent involvement in school, and instruction quality. Furthermore, individual students' cultural identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
(45 reference statements)
3
21
0
Order By: Relevance
“…It is not too surprising that a positive relationship between enculturation and resilience demonstrated in this study is consistent with previous research, which has demonstrated positive relationships between enculturation and resilience among AI adults, reservation-dwelling AI adolescents, and AI college students (Belcourt-Dittloft, 2006;Bergstrom et al, 2003;Huffman, 2001;LaFromboise et al, 2006;Powers, 2006;Resnick et. al., 1997).…”
Section: Results Concerning the Simple Linear Regression Demonstratedsupporting
confidence: 91%
See 3 more Smart Citations
“…It is not too surprising that a positive relationship between enculturation and resilience demonstrated in this study is consistent with previous research, which has demonstrated positive relationships between enculturation and resilience among AI adults, reservation-dwelling AI adolescents, and AI college students (Belcourt-Dittloft, 2006;Bergstrom et al, 2003;Huffman, 2001;LaFromboise et al, 2006;Powers, 2006;Resnick et. al., 1997).…”
Section: Results Concerning the Simple Linear Regression Demonstratedsupporting
confidence: 91%
“…Information concerning plans to complete high school and attend college was also included. The aforementioned criteria have often been used to capture AI resilience by many authorities (Huffman, 2001;LaFromboise et al, 2006;Powers, 2006).…”
Section: Results Concerning the Simple Linear Regression Demonstratedmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Taylor and Wright (2003) found that receiving instruction in traditional Indigenous languages provided Inuit students in Nunavik "significant academic and linguistic advantages" (p.13). Powers (2006) found that culture-based programming in schools affected urban Indigenous students' educational outcomes, and there was a stronger association among students who most strongly identified with their culture (see also Powers, Potthoff, Bearinger & Resnick, 2003). Indigenous curricular content as well as traditional Indigenous methods of teaching and learning are also seen to contribute to Indigenous student self-confidence, self-esteem, and cultural identity (McDonald, 2011;Taylor & Wright, 2003).…”
mentioning
confidence: 99%